Efeito anti-helmíntico da suplementação com Mimosa Caesalpiniifolia em caprinos submetidos a uma floresta tropical decídua - PINTO, Nathalie Silva (2018)
The inclusion of products and by - products of plants rich in tannins in the diet of small ruminants is an alternative in the control of Haemonchus contortus, due to the resistance of the parasites to the traditional treatment based on the use of chemical bases. The use of deciduous tropical forests (FTD) is an important resource in goat production, due to the great diversity of fodder plants rich in protein and condensed tannins, which may be important in the control of gastrointestinal nematodes. However, as this heterogeneous vegetation undergoes drastic changes due to the climatic effect, occurring changes in the availability of food throughout the year, it is worth to evaluate the effect of a supplementation in animals submitted to it. The objective of this study was to evaluate the effect of Mimosa caesalpiniifolia supplementation on H. contortus in goats under grazing on FTD. To confirm the in vitro activity of the M. caesalpiniifolia sample, egg hatchability tests and larval sampling were performed. Twenty-four male, castrated, Anglo-Nubian mestizos, six to eight months old, were infected with a single dose of 4000 infective larvae of H. contortus 28 days before the start of the experiment. The animals spent one week in adaptation to the experimental diet, after which they were distributed in two groups according to the egg count per gram of feces (OPG) and body weight. Group I: infected animals receiving a daily supplement containing M. caesalpiniifolia (128.7 mg of condensed tannin (CT) / kg) and Group II: infected animals receiving a daily supplement without M. caesalpiniifolia, both groups will have access to heterogeneous vegetation from 8:00 am to 4:00 p.m. All animals received isoprotein and isoenergetic supplementation. The FEC were carried out three times a week. In addition, an egg hatchability assay was performed once a week for both groups. The direct observation method was applied in 4 goats to record the species of plants consumed and categories of bite (CB), through audio recordings. The pasture circuits lasted 8 hours per day, four days of observation were carried out. After 28 days of experimental feeding, all animals were slaughtered humanely and adult worms were counted. In the in vitro assay, a 90.27% and 86.12% draw inhibitory effect was observed at the concentrations of 1.2 mg / ml and 0.6 mg / ml, respectively. After treatment with 10 mg / ml (higher concentration) an inhibitory effect of 42% was observed in the hatchability test. There was no effect of the experimental diet on weight gain and the efficiency of the FECR reduction was 25.1% in the supplemented group compared to the supplemented group in the last week of the experiment. There was no significant effect of M. caesalpiniifolia supplementation on the reduction of the number of adults. (P> 0.05). A total of 20 species of FDT plants were consumed. The medium values of DMI was 133.7 g/day for tannin supplemented animals and 68.9 g/day for tannin non-supplemented animals, it was significantly difference (P<0.05). The intake of CP (g/DM/day) for tannin supplemented animals was greater than for tannin non-supplemented animals, medium values were of 14.2 and 6.2, respectively (P<0.05). Tannin supplemented animals ingested 7.1 g/day and non-supplemented animals ingested 4.1 g/day of TC in TDF (P>0.05). There is significant potential in the use of M. caesalpiniifolia in the goat diet for the control of H. contortus, but there is a need for further studies to clarify in more detail how the anthelmintic effect of tannins or other polyphenols present in the plant under study, develops. The use of an FDT is a possible alternative in the nutrition of goats, but it depends on the knowledge about the quality of the diet and the nutrient balance.